2010
DOI: 10.1080/09602011003710993
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Oral Re-reading treatment for alexia: The parts may be greater than the whole

Abstract: This study examines the reasons for the success of Multiple Oral Re-reading (MOR; Moyer, 1979), a non-invasive, easily administered alexia treatment that has been reported in the literature and is currently in clinical use. The treatment consists of reading text passages aloud multiple times a day. Findings that MOR improves reading speed on practiced as well as novel text have been inconsistent, making MOR‘s role in the rehabilitation of alexia unclear. We hypothesized that MOR’s treatment mechanism works thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Lacey and colleagues (Lacey 2007;Lacey et al, 2010) showed that carefully controlled generalisation passages could help to identify specific therapy effects and demonstrate how MOR therapy facilitated reading. This highlights the need for a greater understanding of the potential benefits of individual therapy techniques (and mechanism of change) so that measures can be designed which are sensitive to those changes.…”
Section: Reading Abilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Lacey and colleagues (Lacey 2007;Lacey et al, 2010) showed that carefully controlled generalisation passages could help to identify specific therapy effects and demonstrate how MOR therapy facilitated reading. This highlights the need for a greater understanding of the potential benefits of individual therapy techniques (and mechanism of change) so that measures can be designed which are sensitive to those changes.…”
Section: Reading Abilitymentioning
confidence: 98%
“…MOR is not focused on reading comprehension per se, and the majority of participants are reported to have good or functional comprehension prior to therapy; participants generally report slow reading speed which interferes with their everyday reading. These studies have demonstrated improved reading rate on trained passages and generalisation (of this improved rate) to untrained passages, particularly those with some overlap with the trained stimuli (Lacey, 2010). In contrast, ORLA therapy, initially described by Cherney, Merbitz, and Grip (1986), was designed to improve comprehension.…”
Section: Introductionmentioning
confidence: 96%
“…Three individuals with acquired language impairment following stroke participated in this study, and their performance was compared with that of 10 healthy adults 1 MOR and other oral reading treatments have also been implemented in individuals with reading deficits associated with aphasia and phonological impairment due to left perisylvian damage (e.g., Beeson & Insalaco, 1998;Cherney, Merbitz, & Grip, 1986;Lacey et al, 2010), but that is not the focus of this article. on various tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The supported reading stimulation from MOR has a rehabilitative effect so that reading rate and accuracy are better for untrained text, and word-form recognition improves as evidenced by a reduced word-length effect. A recent review of MOR treatment by Starrfelt, Olafsdóttir, and Arendt (2013) examined treatment outcomes from seven cases reported in four studies since 1990 (Beeson, 1998;Beeson et al, 2005;Lacey et al, 2010;Tuomainen & Laine, 1991). Four of the cases showed significant improvement in reading speed for words and/or text, and one individual (RB in Beeson et al, 2005) showed a significant improvement in reading rate for unfamiliar text and a resolution of the word-length effect by the end of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation